Comparative In Vitro Activity of Ceftazidime-Avibactam, Imipenem-Relebactam, and Meropenem-Vaborbactam against Carbapenem-Resistant Clinical Isolates of Klebsiella pneumoniae and Pseudomonas aeruginosa - Anthony Sophonsri; Michelle Kalu; Annie Wong-Beringer (MDPI AG, 2024)
Co-infection with carbapenem-resistant Klebsiella pneumoniae (CRKP) and Pseudomonas aeruginosa (CRPA) is associated with poor outcomes and historically relied on combination therapy with toxic agents for management. However, several novel β-lactam/β-lactamase inhibitor combination agents have been developed, offering potential monotherapy options. Here, we compare the in vitro activity of ceftazidime-avibactam (CZA), imipenem-relebactam (IRL), and meropenem-vaborbactam (MVB) against both CRKP and CRPA clinical isolates. Minimum inhibitory concentrations (MICs) for each agent were determined using broth microdilution. Carbapenemase gene detection was performed for representative isolates of varying carbapenem resistance phenotypes. IRL demonstrated excellent activity against CRKP and CRPA with susceptibility rates at 95.8% and 91.7%, respectively. While CZA and MVB showed comparable susceptibility to IRL against CRKP (93.8%), susceptibility of CRPA to CZA was modest at 79.2%, whereas most CRPA strains were resistant to MVB. Of the 35 CRKP isolates tested, 91.4% (32/35) carried a blaKPC gene. Only 1 of 37 (2.7%) CRPA isolates tested carried a blaVIM gene, which conferred phenotypic resistance to all three agents. None of the CRKP strains were cross-resistant to all three agents. Source of infection and co-infection did not significantly influence antimicrobial activity for IRL and CZA; none of the CRPA isolates from co-infected patients were susceptible to MVB. Our results suggest that novel β-lactam agents with antipseudomonal activity and stability against carbapenemases, such as IRL and CZA, offer potential monotherapy options for the treatment of co-infection involving both CRKP and CRPA, but not MVB.